2010
DOI: 10.1902/jop.2010.090441
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Angiogenic Activity of Enamel Matrix Derivative

Abstract: EMD stimulates angiogenesis in the CAM model. As a heterogeneous mixture of extracellular matrix components, EMD may have multiple biologic functions, but it is likely that at least part of the explanation for its observed positive clinical effects may be the stimulation of angiogenesis. The fact that vascularity was also increased by recombinant human amelogenin raises the possibility that this 28.9-kDa protein may be the source of the angiogenic activity because it is the predominant protein of the EMD mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
(48 reference statements)
4
27
0
Order By: Relevance
“…In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31]. Furthermore, recent research from Cochran's group has provided evidence for angiogenic properties of enamel matrix proteins which may substantially improve vascularization and future wound healing [36]. Our group has also previously characterized the combination of EMD delivered in a PGA carrier on new bone formation in the same animal model where it was also found that EMD improved new bone formation [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31]. Furthermore, recent research from Cochran's group has provided evidence for angiogenic properties of enamel matrix proteins which may substantially improve vascularization and future wound healing [36]. Our group has also previously characterized the combination of EMD delivered in a PGA carrier on new bone formation in the same animal model where it was also found that EMD improved new bone formation [6].…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported that more endothelial cells and new blood vessels were detected in cell cultures treated with EMD than in control group 56) . Several authors have indicated that EMD has angiogenic activity at the applied sites 57) , and it can stimulate periodontal cells to produce VEGF 58) . However, Darwish et al suggested that enamel matrix derivative, could be preferable material for periodontium, while it is not suitable for dentin-pulp complex regeneration 59) .…”
Section: The Effect Of Dental Treatments and Materials On Angiogenesimentioning
confidence: 99%
“…Porcine enamel matrix derivate (EMD), containing extracted amelogenins, have been found to regenerate periodontal tissues like periodontal ligament (PDL), cementum and alveolar bone [8], and is used clinically in dentistry to treat periodontal defects [9], and also in the treatment of leg ulcers [10]. A positive effect on bone regeneration has also been seen in rat femur and skull [11][12], and amelogenin has been reported to have positive effects on angiogenesis and wound healing in animal models [10], [13][15]. So far the clinical applications of amelogenin are limited to treatment of periodontal defects and leg ulcers, but increased clinical use may be expected in the future [16].…”
Section: Introductionmentioning
confidence: 99%